2018
DOI: 10.1007/s12602-018-9466-z
|View full text |Cite
|
Sign up to set email alerts
|

Selection and Evaluation of Probiotic and Functional Characteristics of Autochthonous Lactic Acid Bacteria Isolated from Fermented Wheat Flour Dough Babroo

Abstract: The present study aimed to isolate and identify the potential probiotic lactic acid bacteria (LAB) from traditionally fermented wheat flour dough known as "babroo." A total of 26 lactic isolates were obtained from 50 different samples collected from different locations of the Himalayan province (Himachal Pradesh). To ascertain non-pathogenic nature, the isolates were screened by hemolytic activity leading to 20 non-hemolytic strains which were subjected to tolerance to simulated gastrointestinal conditions. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 40 publications
0
24
1
Order By: Relevance
“…Although some studies [44,47,48] reported the direct correlation between bacterial cell surface hydrophobicity and auto-aggregation capability, the results of this study do not support the hypothesis as relation of the autoaggregation and CSH was not characterized.…”
Section: Discussioncontrasting
confidence: 98%
“…Although some studies [44,47,48] reported the direct correlation between bacterial cell surface hydrophobicity and auto-aggregation capability, the results of this study do not support the hypothesis as relation of the autoaggregation and CSH was not characterized.…”
Section: Discussioncontrasting
confidence: 98%
“…69 Refered to the potential dissemination of the resistance mediated by genetic mechanisms, such as horizontal gene transfer where plasmids, transposons and integrons may be involved, [97][98][99][100][101] is essential to evaluate the susceptibility patterns of potentially probiotic bacteria. 102 Microbial resistance to clinically relevant antibiotics must be absent as part of the QPS assessment of bacteria deliberately introduced into the food chain. 103 Also it is important to screen the enzymes acting as potential virulence factors, as hydrolytic enzymes (hemolysin, lecithinase, gelatinase, etc.)…”
Section: Most Of the Probiotic Lactobacilli Are Considered As Generallymentioning
confidence: 99%
“…Utilizing onion peel fermented with LAB to produce functional food revealed some potential to regulate blood pressure [41]. Commercially available L. plantarum fermented juices have adequate antioxidants, antimicrobials, and anti-inflammatory properties [42]. Recently, phylogenetic analysis revealed that strains of Lactobacillus fermentum and L. plantarum, with two strains of Pediococcus acidilactici, exhibited different degrees of cell surface hydrophobicity and cholesterol-lowering activity [42].…”
Section: Nutraceuticals From Bacterial Originmentioning
confidence: 99%
“…Commercially available L. plantarum fermented juices have adequate antioxidants, antimicrobials, and anti-inflammatory properties [42]. Recently, phylogenetic analysis revealed that strains of Lactobacillus fermentum and L. plantarum, with two strains of Pediococcus acidilactici, exhibited different degrees of cell surface hydrophobicity and cholesterol-lowering activity [42]. Consequently, O22, O24, L. rhamnosus K3, and L. plantarum O20 are four tested strains that revealed the ability to induce anti-inflammatory mediators, balancing between regulatory and pro-inflammatory cytokines, with the potential to improve the host immunity [43].…”
Section: Nutraceuticals From Bacterial Originmentioning
confidence: 99%